Mapping The Risk Level of Earthquake Damage in Central Java Based on Data From PGA, PD and HDI - Abdul Basid; Rusli Rusli; Purwandari Purwandari (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2021)
Central Java is one of the provinces in Indonesia with a fairly high level of seismicity. During January 2021 alone there were 22 tectonic earthquakes, one of which occurred in Banyumas (M.5). With this fairly high seismicity, it is necessary to reduce its impact through mitigation. One of the efforts that can be done is to map the level of risk of damage. This mapping can be made based on the Peak Ground Acceleration (PGA) value combined with the Population Density (PD) and Human Development Index (HDI) values. Two methods were used to calculate PGA based on the 1970-2020 earthquake data, namely the Crouse (1991) and Donovan (1973) methods. The results of the calculation using the Crouse method obtained the highest PGA value of 92–180 gal (VI-VII MMI) and the Donovan method obtained the value of 92-107 gal (VI MMI). From this PGA value combined with the PD and HDI values in each district in Central Java, a map of the level of risk of damage caused by the earthquake is made. The results of the mapping show that the districts of Klaten, Cilacap, Kebumen, Banyumas, Brebes, Magelang, Demak and Semarang have a fairly high risk of damage.